A figurational perspective on the comparison of three national judo systems - Nolte, P. L.; Burnett, C. (Journal of Physical Education and Sport, 2020)
This paper draws on a doctoral study relating to the management of national sport organisations in a global commercialised context. Within this increasingly global, commercialised and professionalised context, governments are investing significant resources to capitalise on the potential socio-economic and political benefits that could be derived from elite sport participation. Subsequently, the resources of elite sport systems are strategically managed to achieve specific performance outcomes. Therefore, this research addresses the following question: How does that management of national elite sport systems compare in a globalised and commercialised sports context? This descriptive, inter-case comparative analysis involves a transnational concurrent mixed-methods research design. Interviews with a purposive sample of ten key decision-makers include coaches from Judo South Africa (n=3), the British Judo Association (n=3) and the Netherlands Judo Federation (n=2), and one executive member from Judo South Africa and the British Judo Association (n=2). Main findings include that a figurational analysis of global and national influences translated into differential degrees of professionalization of judo systems in support of key competitive outcomes with strategic management, human resource development and access to high quality physical resources. In the context of professionalised elite sport systems, these factors combine to varying degrees in order to provide athletes with access to highly efficient long-term athlete development programmes. Evidently, managers should capitalise on available resources within their unique sociocultural, economic and political environments. This paper informs current discourses, illuminates possibilities for future research, and offers insights for strategic decision-making within the open, dynamic environments of elite sport systems.